Associations Between the Polymorphisms in the Coding Sequence of SLCO1B1 and Blood Lipid Levels Before and After Treatment by Atorvastatin in the Chinese Han Adults with Dyslipidemia - Chen C; Tian Y; Jia F; Feng M; Zhang G; Li Q; Zhang Y; Sun N; Hu S; Ji Z (Pharmacogenomics and Personalized Medicine)
Chao Chen,1,* Yan Tian,2,* Fengshun Jia,1,* Mingkun Feng,1 Guoqiang Zhang,2 Qian Li,2 Yanwei Zhang,3 Ningling Sun,4 Songnian Hu,5,6 Zheng Ji1 1Department of Cardiology, Tangshan Gongren Hospital, Tangshan, Hebei, People’s Republic of China; 2Beijing HuaGengYuan Pharmacogenomics Research Institute Co. Ltd., Beijing, People’s Republic of China; 3Beijing E-Seq Medical Technology Co. Ltd., Beijing, People’s Republic of China; 4Institute of Hypertension, People’s Hospital, Peking University, Beijing, People’s Republic of China; 5State Key Laboratory of Microbial Resources, Institute of Microbiology, Chinese Academy of Sciences, Beijing, People’s Republic of China; 6University of Chinese Academy of Sciences, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zheng Ji; Songnian Hu, Email jizheng999@163.com; husn@im.ac.cnPurpose: Atorvastatin is commonly used to treat dyslipidemia; however, individual responses vary considerably. This study endeavors to evaluate the relationship between polymorphisms in the coding sequence (CDS) of SLCO1B1 gene and blood lipid levels before and after atorvastatin treatment among the Chinese Han adults with dyslipidemia.Patients and Methods: A total of 165 Chinese Han adults undergoing atorvastatin therapy were enrolled in this study and followed up quarterly. The complete CDS of the SLCO1B1 gene was sequenced to detect polymorphisms. Statistical analysis was utilized to assess the impacts of sex, age, body mass index (BMI), and polymorphisms on blood lipid levels before and after atorvastatin treatment.Results: Fourteen polymorphisms were identified in the SLCO1B1 CDS. Among them, four polymorphisms had mutant alleles present in over 20 patients. No polymorphism was found to correlate with blood lipid levels before treatment; in contrast, age, sex, and BMI did show correlations (P< 0.05). Notably, females had higher baseline blood lipid levels than males, indicating that sex had a more significant impact on baseline levels than age and BMI. The polymorphism rs2306283 was significantly correlated with the efficacy of atorvastatin (P< 0.05), whereas age, sex, and BMI were not. Carriers of the rs2306283 AA allele experienced a substantially greater reduction in total cholesterol (TC) and triglyceride (TG) levels after atorvastatin treatment. The other polymorphisms did not demonstrate any significant impact on atorvastatin’s efficacy.Conclusion: This study delved into the intricate genetic structure of polymorphisms in SLCO1B1 CDS and their roles in lipid metabolism and atorvastatin’s efficacy among Chinese Han adults with dyslipidemia. The findings underscore the crucial role of the rs2306283 polymorphism in the response to atorvastatin’s efficacy, highlighting the significance of pharmacogenomics in personalized medicine. It is thus advisable to consider genetic testing for SLCO1B1 variants to optimize atorvastatin therapy.Keywords: pharmacogenomics, SLCO1B1 polymorphisms, atorvastatin, dyslipidemia, Chinese Han